Design, prototyping and testing of a modular small-sized underwater robotic arm controlled through a Master-Slave approach. (15th June 2018) - Barbieri, Loris; Bruno, Fabio; Gallo, Alessandro; Muzzupappa, Maurizio; Russo, Maria Laura
Abstract: Underwater exploration, in the last years, has evolved toward a wide adoption of increasingly smaller ROVs (Remotely Operated Vehicle). As a consequence, the need to equip these underwater vehicles with robotic arms is currently rising as well. According to this demand, the paper presents three innovative solutions achieved in the UVMS (Underwater Vehicle-Manipulator System) field. Firstly, the paper proposes a modular architecture for a lightweight underwater robotic arm, which can be mounted on small-sized ROVs. The modular concept of the arm enables several different configurations, each one characterized by the related DOFs, deployed according to the type of application to be performed. Secondly, the arm has been equipped with an adaptive gripper that, taking advantage of the additive manufacturing techniques, is able to easily grip differently shaped objects. Lastly, the underwater arm is controlled through a Master–Slave approach, designed for commercial off-the-shelf electronics, that on the one hand, entailed a significant reduction of the bill of materials, but, on the other hand, required a greater effort in the software development. Experimental tests have been carried out to measure and evaluate the gripping and manipulation capability of the robotic arm and the performance of the proposed control system. Highlights: Three innovative solutions achieved in the UVMS field are presented. A modular lightweight underwater robotic arm for small sized ROVs is proposed. A 3d printed adaptive gripper for small sized ROVs is proposed. A Master–Slave approach designed with off-the-shelf electronics is proposed.